DEVELOPMENT AND EVALUATION OF RAFT FORMING GASTRO RETENTIVE FLOATING DRUG DELIVERY SYSTEM OF NIZATIDINE BY DESIGN OF EXPERIMENT - SAGAR, SHANTI; SRINIVAS, LANKALAPALLI (International Journal of Applied Pharmaceutics, 2022)
Objective: The current research involves the formulation of a sustained-release gastro-retentive drug delivery system of nizatidine. Methods: Using 33 Box-Behnken designs, about 17 experiments were performed and evaluated for various parameters like physical appearance, pH, in vitro gelling study, in vitro buoyancy study, measurement of viscosity, density measurement, gel strength, raft resilience, drug content, acid neutralization capacity, in vitro dissolution, release kinetics and stability studies. Results: All the formulations exhibited good viscosity, density less than gastric fluid, gelling capacity retained, and buoyant for 12 h. Drug content ranges from 97.98 to 99.34 %, with a long neutralization period. The buoyancy lag time was found to be in the range of 15.34 to 26.12 sec and the % drug release at 12 h was between range from 85.67 to 99.45, with the highest release exhibited by F3. All formulations displayed zero order in vitro drug release>10 h with exceptional buoyancy properties. F3 was the optimized formulation and further subjected to FTIR and DSC study, concluding that compatibility of nizatidine with excipients in the formulation blend. Stability studies show no significant changes. Conclusion: Results indicate that gastric-floating formulations of nizatidine have the prospective for superior gastric residence time and sustained drug release.